A review on low dimensional carbon desalination and gas separation membrane designs - Ang, Elisa Yun Mei (2022)
The widespread use of low dimensional carbon membrane for desalination and gas separation is limited by the difficulty to physically realise such membrane designs on a meaningful scale. This review aims to bring together results achieved in this field, hoping to inspire new designs or developments that could bridge this technical challenge. The focus of this paper is on sub-nanometer separation operations such as desalination or gas separation. This is because such operations consume the most energy, and there is thus much interest to reduce this cost. Three groups of low dimensional carbon materials are considered: graphene, carbon nanotubes (CNT) and graphene oxide (GO). Graphene and CNT membranes have the advantage of high permeability but are difficult to manipulate to form membranes that separate efficiently. GO, on the other hand, has the advantage of ease of fabrication but suffers in terms of separation performance. This review dives deep into the innovative ideas proposed for these low dimensional carbon membrane design, deliberating their strengths and weaknesses, in a consolidated effort to generate new ideas for further advancements.